I asked this question earlier: find x for log₂(4.3ˣ-6)-log₂(9ˣ-6)=1

I understand the first part, but do not understand the substitution.

Can someone please thoroughly explain the steps after let u=3ˣ ?

Please and thank you

Because 9^x = (3^2)^x, when we substitute 3^x as u , 9^x will become u^2

3^{x} =u

9^{x} = (3^{2})^{x} = 3^{2x} = (3^{x})^{2} = u^{2}

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up